Limited Access to Dermatology Specialty Care: Barriers and Teledermatology - Darlla Duniphin (Mattioli1885, 2023)
Introduction: Access to dermatology specialty care is limited in the underserved population. Barrier identification and exploring the potential role of teledermatology are the first steps to address this problem.  Objectives:  Identify the barriers to dermatologist care for diagnosis and treatment of melanoma and non-melanoma skin cancers in the underserved population.  Additionally explored was the potential role of teledermatology to provide dermatology care access in the underserved population.   Methods:  A quantitative descriptive study was conducted via an online survey instrument.  The survey's barriers portion was adapted from the 1998 Ohio Family Health Survey (OFHS).  The survey's teledermatology portion was adapted from the McFarland Teledermatology Provider and Imaging Technician Satisfaction Survey.  The participants were practicing dermatologists and members of Georgia, Missouri, Oklahoma, and Wisconsin dermatology associations.  Thirty-eight responded to demographic questions, of which twenty-two responded to the survey items.  Results: The top three barriers ranked as the most concerning were continually uninsured (n = 8; 36.40%), resides in a medically underserved county (n = 5; 22.70%), and family under federal poverty level (n = 7; 33.30%).  Teledermatology as a potential role for access to care was supported by convenient delivery of healthcare (n = 6; 72.70%), an addition to regular patient care (n = 20; 90.90%), and increase to patient care access (n = 18; 81.80%).  Conclusion:  Barrier identification and teledermatology access to provide care to the underserved population is supported. Further teledermatology research is necessary to address the logistics regarding how to initiate and deliver teledermatology to the underserved.